Penjadualan Produksi n job m mesin Untuk Sistem Produksi Job Shop di Perusahaan dan Industri Mesin Aneka Mesin Malang - Hartono, Moh. (Jurnal Teknik Industri, 2001)
This reseach has to find a production schedule with making a job schedule that have to be done on its machine to minimated makespan and total tardines. In this reseach used branch and brand method because of the reseach location involve the job shop scedulling the use data to find the scedulling is the job proses routing on each machine and its proses time. Than using Computer to acaunt proses casier in its interation/ makespan and total for devises.